Microwave Induced Synthesis and Biological Evaluation of Some Schiff Bases of 2-Amino-3-(N-Chlorophenyl Carboxamido)-4,5-dimethyl Thiophenes - Manjunatha Shetty, K.S.; Somashekar, Vanitha; Mohan, S. (Asian Journal of Chemistry, 2016)
The new series of 2-amino-3-(N-chlorophenyl carboxamido)-4,5-dimethyl thiophenes (I-III) were synthesized by Gewald reaction. Later, the compounds I-III were subjected to treatment with ten different substituted arylaldehydes to yield thirty new Schiff bases (la-j to IIla-j). All the compounds were characterized by spectral data. Antimicrobial activity has been performed using cup diffusion method for all the synthesized compounds. The compounds Ia, IIa and IIIa with 2-chlorophenyl substituent and Ib, IIb and IIIb with 4-chlorophenyl substituent at X exhibited significant antibacterial activity against S. aureus, B. subtilis and E. coli comparable to ampicillin.